Pengaruh Green Motivation, Green Ability, Dan Green Training Terhadap Kinerja Karyawan: Kemampuan Hijau Dan Pelatihan Hijau Terhadap Kinerja Karyawan Dimediasi Oleh Motivasi Hijau - Kurniawan, Muhammad Randhy; Mukharomah, Wafiatun; Satya Pradana, Diky (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2024)
Abstract. This study aims to investigate how employee performance is affected by environmental training and motivation. An example of a quantitative investigation is this one. The study's population and sample were 85 employees of the department of public works and spatial planning in the ngawi regency. The study's data were compiled using primary data sources. strategies for using a questionnaire to collect data. using the data analysis tool Smart PLS. The results of this research demonstrate that whereas green training significantly affects green motivation, green ability has no discernible effect on green motivation. Additionally, whereas green training has no discernible effect on employee performance, green ability has a considerable influence on it. In addition to functioning as a buffer between the detrimental impacts of green ability on employee performance, green motivation also has a substantial influence on employee performance. Keyword: green ability, green training, green motivation, employee performance.